Psychometric Testing of a Value-Achievement-Cost Motivation Survey for 12th Grade Health Sciences Students for Use in Simulation-Based-Games. (December 2019) - Glover, Kevin R.; Bodzin, Alec
Background . There is a gap in our understanding of the determinants of individual student variation of perceivedcost longitudinally in high-effort educational activities within self-selected, context-specific academic domains using the Expectancy-Value framework. At present, an instrument to conduct such research on themotivational dynamics of students who choose to persist in highcost behaviors to achieve mastery inhealth sciences multi-levelsimulation-based-games is lacking. Method . In this study, a 10-construct, 46-itemValue-Achievement-Cost (VAC) studentmotivation survey was administered on two separate occasions to 44 12 th grade students who had self-selected to participate in a year-long, dual enrollment, health-sciences, Career and Technical Education (CTE) program. The VAC survey was used to measuremotivation associated with science in general, health sector science learning, and playinghealth sciences -related games. Results . Convergentvalidity was established in five of the ten constructs by comparing the α coefficients of the modified 10-construct, 46-item VAC survey compared to three source instruments previously tested in dissimilar STEM student populations. Internal consistency for each of the 10 VAC survey constructs were strong with α coefficients between 0.82 and 0.90. The VAC survey exhibitedreliability between the two administration timepoints with statistically significant nonparametric correlation coefficients in forty-four of the 46-items tested displaying strong monotonic relationships between 0.30 and 0.79. Conclusion . This study has provided the psychometric evidence needed so that the VAC survey can be confidently used to assess cost-related motivational dynamics in longitudinalhealth science multi-levelsimulation-based-games . An experimental intervention correlating VAC survey measures withhealth-science students' achievement in a simulation-based, multi-level game is proposed. Students'value, achievement, andcost motivation, related to level achievement, may lead to a better understanding of whichhealth-science game design elements encourage learners to independently persist to mastery.